Photonic crystal fiber tip interferometer for refractive index sensing - Zhang, Taishi (2013)
In this paper we present an interferometer based on photonic crystal fiber (PCF) tip ended with a solid silica-sphere for refractive index sensing. The sensor is fabricated by splicing one end of the holey PCF to a single mode fiber (SMF) and applying arc at the other end to form a solid sphere. The sensor has been experimentally tested for refractive index and temperature sensing by monitoring its wavelength shift. Measurement results show that the sensor has the resolution of the order of 8.7×10 −4 over the refractive index range of 1.33–1.40, and temperature sensitivity of the order of 10  pm/°C in the range of 20–100 °C.